Odpowiedź:
1. mnożymy na krzyż.
(x-3) * (x+2) = (x +3) *(x-2)
[tex]x^{2}[/tex] - 3x + 2x - 6 = [tex]x^{2}[/tex] - 2x + 3x - 6
[tex]x^{2}[/tex] - x - 6 = [tex]x^{2}[/tex] + x - 6
[tex]x^{2}[/tex] - [tex]x^{2}[/tex] - x - x = 0
x = 0
2.
[tex]\frac{4}{x}[/tex] = [tex]\frac{3}{2}[/tex] + 8 // * x
4 = [tex]\frac{3}{2}[/tex] x + 8 x // *2
8 = 3 x + 16 x
19 x = 8 // : 19
x = [tex]\frac{8}{19}[/tex]
3.
2x + 4 = (2 x - 1 ) * (x -1)
2x + 4 = 2[tex]x^{2}[/tex] - 2 x - x +1
2[tex]x^{2}[/tex] + 2x + 3x + 3 = 0
2[tex]x^{2}[/tex] + 5x + 3 = 0
Δ = 25 - 24
Δ = 1
x = [tex]\frac{-5 - \sqrt{1} }{4}[/tex] oraz x = [tex]\frac{-5 + \sqrt{1} }{4}[/tex]
Szczegółowe wyjaśnienie: